ANALISIS PENGARUH DAYA TARIK WISATA KULINER DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG KEMBALI DI PASAR LAMA TANGERANG - irena, Florencia; Sarudin, Rendy (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the factors that influence the relationship between Culinary Tourism Attractiveness and Destination Image on Interest to Return and how much influence Culinary Tourism Attraction and Destination Image have on intention to return to the Old Market in Tangerang. This study uses a descriptive quantitative approach. Methods of data collection using questionnaires, observation and documentation. The number of respondents was 100 according to the criteria of respondents who visited the Tangerang Old Market at least twice by determining the sample using purposive sampling. Methods of data analysis in this study using multiple linear regression analysis. The test results used the IBM SPSS Version 27 program. The results of this study found that : (1) Culinary Tourism Attractiveness and Destination Image have a positive and significant simultaneous influence on the Interest to Return to the Old Market in Tangerang as evidenced by the results of the t test of 0.001 <0.05. (2) From the results of multiple linear regression worth Y = 2.662 + 0.102 + 0.500 (3) From the results of R Square worth 71.2% which states that it is influential and the remaining 28.8% is influenced by other variables not examined.